R&D profitability: the role of risk and Knightian uncertainty - Sara Amoroso; Pietro Moncada-Paternò-Castello; Antonio Vezzani (European Commission, Joint Research Centre (JRC), 2015)
This paper provides the first empirical attempt of linking firms' profits and investment in R&D revisiting Knight's (1921) distinction between uncertainty and risk. Along with the risky profit-maximizing scenario, identifying a second, off-setting, unpredictable bias that leads to heterogeneous returns to R&D investments is crucial to fully understand the drivers of corporate profits.
Keywords: O30; D22; D81; 330; Corporate R&D investment; firms' operating profits; Knightian uncertainty; ambiguity.